The first complete chloroplast genome of medical plant Terminalia neotaliala. Issue 3 (2nd July 2020) - Huang, Jie; Wee, Alison Kim Shan
Abstract: Terminalia neotaliala, a tropical tree species that originated from Madagascar, is a plant of high medical and horticultural value in Africa and China. This is the first study to present the complete chloroplast genome of T. neotaliala . The total chloroplast genome was 159, 439bp in length, consisting of a large single copy (LSC) with 88, 832bp, a small single copy (SSC) region of 19, 013bp, and two inverted repeat (IRs) regions of 25, 797bp. The overall GC content in the chloroplast genome was 36.9% and that of LSC, SSC and IRs were 34.7%, 30.5% and 43.0%, respectively. Of the 141 annotated genes, 96 were coding genes, eight were rRNA genes and 37 were tRNA genes. A phylogenetic analysis showed that in Myrtales, T. neotaliala is closely related to Laguncularia racemosa and Lumnitzera littorea .